The Abbé Grégoire and his World
XV, 200 p.
Keywords: A distinguished group of international scholars from the disciplines of history, philosophy, literature and art history offer a reconsideration of the ideas and the impact of the abbé Henri Grégoire, one of the most important figures of the French Revolution and a contributor to the campaigns for Jewish emancipation, rights for blacks, the reform of the Catholic Church and many other causes.